Active women demonstrate acute autonomic and hemodynamic shifts following exercise in heat and humidity: A pilot study. Issue 1 (2nd January 2021) - Zabriskie, Hannah A.; Kerksick, Chad M.; Jagim, Andrew R.
ABSTRACT: The purpose of this study was to assess autonomic and hemodynamic recovery in women who performed moderate-intensity exercise in heat. Seven women (31.7 ± 7.6 years, 67.5 ± 4.4 kg, 25.7 ± 5.6% Fat, 43.9 ± 5.1 mL/kg/min) completed two identical bouts of graded treadmill walking (~60% VO2 peak). One bout was hot (37.5 ± 1.4°C, 46.5 ± 4.6% relative humidity (RH)), and the other was moderate (20.7 ± 1.1°C, 29.9 ± 4.1% RH). For 24 h before and one h after each bout, participants had heart rate variability monitored. After each exercise bout HR and BP were measured during 30 min of supine recovery and 10 min of orthostatic challenge. HF power and RMSSD were lower and LF power and LF:HF ratio greater following exercise in the heat and remained different from the moderate condition for 30 min (p < 0.05). During supine recovery, heat exposure led to higher HR (p = 0.002) and lower DBP (p = 0.016). SBP (p = 0.037) and DBP (p = 0.008) were both lower after 10 min of supine recovery following hot exercise than after moderate temperature. Average response did not reveal orthostatic hypotension despite heat causing a higher HR (p = 0.011) and lower SBP (p = 0.026) after 10 min of orthostatic exposure. Trained women exhibit an autonomic shift toward sympathetic dominance for at least 30 min after exercise in heat. Women who exercise in heat should be wary of an exacerbated HR response after exercise and low recovery blood pressures.